Missionary Cao Mingdao and the Women’s Missionary Work of the China Inland Mission in Wenzhou - CHEN, Fengsheng (Journal of Research for Christianity in China (JRCC), 2025)
This article examines the life and contributions of missionary Cao Mingdao to the women’s missionary work of the China Inland Mission in Wenzhou. It first outlines Cao Mingdao’s family background and marital history, then analyzes her contributions to women’s education, ministry to the blind, and the foot-binding reform movement in Wenzhou.